Front Cover: Wide‐field monitoring and real‐time local recording of microvascular networks on small animals with a dual‐raster‐scanned photoacoustic microscope. Issue 6 (1st June 2020) - Yang, Fei; Wang, Zhiyang; Zhang, Wuyu; Ma, Haigang; Cheng, Zhongwen; Gu, Ying; Qiu, Haixia; Yang, Sihua
Abstract: A dual‐raster‐scanned photoacoustic microscope (DRS‐PAM) was reported, which integrates a two‐dimensional motorized translation stage for large field‐of‐view imaging and a two‐axis fast galvanometer scanner for real‐time imaging. The DRS‐PAM provides a flexible transition from wide‐field monitoring the vasculature of organs to real‐time imaging of local dynamics. Further details can be found in the article by Fei Yang, Zhiyang Wang, Wuyu Zhang, et al. (e202000022 ). Abstract : A dual‐raster‐scanned photoacoustic microscope (DRS‐PAM) was reported, which integrates a two‐dimensional motorized translation stage for large field‐of‐view imaging and a two‐axis fast galvanometer scanner for real‐time imaging. The DRS‐PAM provides a flexible transition from wide‐field monitoring the vasculature of organs to real‐time imaging of local dynamics. Further details can be found in the article by Fei Yang, Zhiyang Wang, Wuyu Zhang, et al. (e202000022 ).